Identity, nationhood and migrations to Turkey from the Balkans, 1950-1960 - ERKEN, ALİ (WILEY, 2022)
The article examines identity politics in Turkey through migrations from the Balkans in the early years of Cold War. Despite secularisation reforms in the 1920s and 1930s, Muslim identity remained a central component in the formation of Turkish nationhood. In the wake of WW II, Turkey chose to be a part of Western world whereas her two regional neighbours, Bulgaria and Yugoslavia, remained in the Socialist bloc. Nearly 500,000 Turks, Bosnians, Albanians and Pomaks in Yugoslavia and Bulgaria were either forced, or encouraged, to leave their lands after 1950. Despite ideological barriers and ethnic differences, Turkey welcomed these migrants to the country. Official records, recently available biographies and oral sources shed light on the discourses of identity politics through this period.
Keywords: YUGOSLAVIA